Atividades didáticas como ferramentas facilitadoras na compreensão de imagens da divisão celular - Tatsch, Helene Mochetti (2016)
Images are teaching resources widely used in education. Especially in biology, they are very useful to register form and structure of organisms and to represent the cellular processes. The overall aim of this dissertation was to investigate how the records and representations through images, also can be a source of misconceptions. The specific objectives of the study were to evaluate the recognition and interpretation of images of mitosis and propose educational activities that would help in the development of interpretation skills. The sample of this research was 50 students in the first year of high school. The activities were developed in two schools, one private school and one public school). The research was divided into three stages; the first one was the application of diagnostic activities using: i) a sequence of images of cell division, to investigate the recognition of phases of mitosis; ii) modeling clay to know how the students represent a chromosome. Difficulties in recognition of images and concepts about the structure of chromosomes were analyzed. After the diagnostic activities was applied a set of educational activities about the mitosis. Two ludic activities (card game and puzzle) and two practical classes (observation of mitosis in onion roots and tridimensional model of metaphase) were associated for presentation and discussion of the phases of the mitosis. At the end of the activities the students carried out the assessment of the set of educational proposals and answered questions about interpretation of images related to mitosis and chromosomes. At diagnostic activity was detected that students still have difficulty in recognizing the images produced by microscopy. The construction of chromosomes with modeling clay revealed that most students believe that the chromosomes have the shape of X. This concept was resistant and remained even after the presentation of the set of educational activities. The students were highly motivated and rated as very positive all the activities presented. The application of these activities had positive results for the understanding of the spatial distribution of chromosomes in mitosis and permited more effective association between microscopy and simplified representations of images. These results reinforce the ideas about the need to diversify the forms and methods of presentation of abstract content related to cellular processes and the importance of working with the images generated from microscopy to assist the development of interpretation skills.